Kebijakan Indonesia pada Era Pemerintahan Presiden Joko Widodo dalam Mewujudkan ASEAN Drug Free Area - Armaghani, Hafizh; Windiani, Reni; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
From national, regional, to international level, the issue of drug abuse becomes one of the most important issues to be resolved. This issue of drug abuse also become a big problem in Indonesia and other countries in Southeast Asia. ASEAN as a regional institution in Southeast Asia region considers this as an urgency that must be handled comprehensively that eventually countries in Southeast Asia have a shared commitment to create a drug-free area. This research contains a discussion of the Indonesian manifestazion to the commitment of ASEAN Drug Free Area in President Joko Widodo era. This study uses the concept of an international regime, which draws conclusions and from data collected in the field. The results of this study show that Indonesia in the era of President Joko Widodo government made efforts in eradicating drugs referring to the work plan of the ASEAN Drug Free Area. The ASEAN Drug Free Area focus in the form of supply and demand reduction is manifested by Indonesia through their national policy. Indonesia is also implementing its policies in accordance with the ASEAN Drug Free Area work plan which is divided into six aspects: (i) Preventive education, (ii) law enforcement, (iii) treatment and rehabilitation, (iv) research, (v) alternative development, and ( vi) law and cooperation.